Using of Calcined Clay in soil subbase materials - Kamal Sharobim; M. EL Gendy; Nesreen Elawadly (Journal of Engineering Research - Egypt, 2018)
The paper presents results of study on soil subbas improvement. The main object of the study was using the recycled calcined clay to get rid of it by a useful friendly environmental method. Big amount of waste refractory bricks were outcome with Portland cement manufacturer. The study presents recycling this waste calcined clay with crushing it into graded aggregates. Coarse crushed (CR) and fine crushed (FR) recycled calcined clay were the products which studied. Kaolin (KA) and Metakaolin (MK) were two other types of calcined clay materials have been studied in this paper to find out it’s suitability as a subbase improvement materials. Two original soil samples were used. The first was an original clayey soil from the surface layer of south Port said, Egypt and the second soil sample was an original sandy soil from the surface layer of Port Fouad, Port Said, Egypt. The scope of the search was to mix original soil with 20% calcined clay. Eight improved samples containing calcined clay with 20% were prepared. Soil properties, sieve analysis and California bearing ratio test (CBR) were checked against the original soil samples. The study recommended recycled calcined clay as an improvement material.